An enigma of hypothyroidism and hyponatremia coexistence: a nationwide population-based retrospective study - Chun-Hao Chu; Wu-Chien Chien; Chiung-Chen Liu; Chi-Hsiang Chung; Ying-Chuan Chen; Feng-Chih Kuo; Hung-Hsiang Fang; Cheng-Yi Cheng; Yi-Xuan Ding; Chiung-Hsi Tien; Chien-Ming Lin (BMC, 2023)
Abstract Introduction Hypothyroidism is a rare and possible cause of hyponatremia. However, the clinical epidemiology and risk of mortality (ROM) when they coexist still remain elusive. Objectives We assessed the epidemiology and ROM among index patients with coexisting hypothyroidism and hyponatremia via a national population database. Patients and methods This retrospective cohort study utilized Taiwan's National Health Insurance program database. Distributions of definite sociodemographic factors were analyzed. The annual incidence among the overall group and sex-subgroups was investigated. In addition, potential factors influencing the ROM were also evaluated. Results Of 4,549,226 patients from 1998 to 2015, a total of 3,140 index patients with concurrent hypothyroidism and hyponatremia were analyzed. The incidence rate increased tenfold from 1998 to 2015; average annual incidence rate was 174. Among the total participants, 57.1% were women; mean age was 72.6 ± 14.7 years and 88.8% were aged > 55 years. Although average length of stay (LOS) was 13.1 ± 15.4 days, the mortality group had significantly longer LOS than that in the survival group (12.9 days vs 22.2 days). Old age, catastrophic illness, cardiac dysrhythmia, and low hospital hierarchy were independent predictors of hospital mortality. The optimal LOS cutoff value for ROM prediction was 16 days. Index patients with LOS > 16 days increased ROM by 2.3-fold. Conclusions Coexistent hypothyroidism and hyponatremia is rare, although the incidence increased gradually. Factors influencing the ROM, such as old age, underlying catastrophic status, cardiac dysrhythmia, hospital hierarchy, and LOS should be considered in clinical care.